2004
DOI: 10.1080/02699200310001596160
|View full text |Cite
|
Sign up to set email alerts
|

Alternating motion rate as an index of speech motor disorder in traumatic brain injury

Abstract: The task of syllable alternating motion rate (AMR) (also called diadochokinesis) is suitable for examining speech disorders of varying degrees of severity and in individuals with varying levels of linguistic and cognitive ability. However, very limited information on this task has been published for subjects with traumatic brain injury (TBI). This study is a quantitative and qualitative acoustic analysis of AMR in seven subjects with TBI. The primary goal was to use acoustic analyses to assess speech motor con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
42
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 33 publications
6
42
0
3
Order By: Relevance
“…palatopharyngolaryngeal myoclonus), the subjects with TBI spent a longer time on each syllable than did the control subjects. This speech motor impairment also explains the limited range of speaking rate adjustment and the slow and irregular AMR performance [23] . Wang/Kent/Duffy/Thomas Although fi nal-syllable lengthening and f 0 downtrend were preserved in subjects with TBI, the prosodic disturbance refl ected by temporal and f 0 components within breath groups was roughly commensurate with speech severity.…”
Section: Discussionmentioning
confidence: 99%
“…palatopharyngolaryngeal myoclonus), the subjects with TBI spent a longer time on each syllable than did the control subjects. This speech motor impairment also explains the limited range of speaking rate adjustment and the slow and irregular AMR performance [23] . Wang/Kent/Duffy/Thomas Although fi nal-syllable lengthening and f 0 downtrend were preserved in subjects with TBI, the prosodic disturbance refl ected by temporal and f 0 components within breath groups was roughly commensurate with speech severity.…”
Section: Discussionmentioning
confidence: 99%
“…Ziegler and Wessel [37] examined 16 individuals with ataxic dysarthria, and reported that speaking rate and AMR exhibited a statistically signifi cant correlation. Nishio/Niimi Wang et al [31] also reported that speaking rate determined during conversation was strongly related to AMR in 7 dysarthric participants after traumatic brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…Specifi cally, AMR involves the rapid repetition of a single syllable, such as /pa/, while the sequential motion rate refers to the rapid repetition of syllable sequences, such as /pataka/ [20] . A slow AMR in speakers with dysarthria has been reported in a series of cross-sectional group studies [5,7,11,14,[21][22][23][24][25][26][27][28][29][30][31] . Longitudinal studies by Kent et al [32] , Yorkston et al [33] , Mulligan et al [34] , and Nishio and Niimi [3] reported slower AMR in individuals with ALS.…”
Section: Introductionmentioning
confidence: 99%
“…DDK rate appears to be a useful index of oral motor development in children [10][11][12][13][14] . DDK has been used as a measure of the speech deterioration in amyotrophic lateral sclerosis [15][16][17] , cerebellar and spinocerebellar damage [8,[18][19][20][21][22] , Friedreich disease [23] , multiple sclerosis [24,25] , Parkinson's disease [25,26] , hemispheric stroke [20,27] , traumatic brain injury [28] , apraxia of speech [29] , and cerebellar mutism syndrome [30] . Slow rate, temporal and intensity irregularities, and inaccuracy in the DDK task are reported in a number of studies on speech impairment associated with a neurogenic disease or damage, including cerebral palsy, developmental dyspraxia, stroke, amyotrophic lateral sclerosis, cerebellar diseases, and basal ganglia disorders [19] .…”
mentioning
confidence: 99%